Devaluated cost: nature, significance and necessity of its use in accounting - D. R. Lapin (Вестник СибАДИ)
The article presents theoretical and practical issues of applying devaluated cost in accounting. The author has revealed the nature and significance of devaluated cost in assessing assets and liabilities. The author on the basis of critical analysis of the content of this concept, presented in the definitions of Russian economists, and the specifics of its use in accounting in accordance with the concept of IFRS, justifies its position regarding this term, formulates its author's definition and proposes an algorithm of actions for correcting the accounting data on the general price index.